The Role of Adversity Quotient (AQ) in Interpersonal Relations of Students and Teachers in Madrasah Aliyah - Hasanusi, Harmathilda; Arafah, Nabilah; Arifidi, Muhammad Ariq; Suryanih (Universitas Muhammadiyah Yogyakarta, 2024)
This research aims to ascertain the role of adversity quotient in interpersonal relationships among students. Intelligence is the ability to change a difficulty into an opportunity for success to achieve a goal. The adversity quotient can predict that students will be able to survive overcoming difficulties and obstacles so they do not give up easily on academic matters. Meanwhile, interpersonal relationships are seen as a process of getting to know someone, which involves personal contact, both physical and psychological, in forming a relationship. In the research methodology, qualitative research was used using interview techniques, observation, and library studies. The population of this study was class XI students and teachers. Then, purposive sampling was employed. While interviews were conducted using structured interviews with a series of structured questions, observations were carried out through direct observation of students and teachers. From the research conducted, the role of adversity quotient in interpersonal relationships between class XI students and teachers at MA Sa'id has been shown to be quite good. Teachers could adjust their approach to students by providing the right motivation, thereby fostering students' adversarial quotient.